2023
DOI: 10.1186/s13071-022-05648-2
|View full text |Cite
|
Sign up to set email alerts
|

Whole-transcriptome profiling across different developmental stages of Aedes albopictus (Diptera: Culicidae) provides insights into chitin-related non-coding RNA and competing endogenous RNA networks

Abstract: Background The Asian tiger mosquito, Aedes albopictus, is one of the most invasive species and a vector of numerous arboviruses. The deleterious effects of long-term and inappropriate use of chemical pesticides have stimulated the exploration of new, environmentally friendly control strategies. Non-coding RNAs (ncRNAs) have been proven to participate in almost all biological processes of insects. Methods In this study, circular RNAs (circRNAs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…CircRNAs, mRNAs, and any other RNAs that share common miRNA response elements (MREs) can competitively bind with miRNAs, acting as an RNA sponge to block and inhibit miRNAs from binding to their target sites ( Tay et al, 2014 ). Studies found that ceRNA regulatory networks are widely present in the growth and development of various insects, such as A. albopictus ( Liu et al, 2023 ), Tetranychus cinnabarinus ( Feng et al, 2022 ), B. mori ( Yin et al, 2021 ). Here, we noticed that 19 DEcircRNAs (novel_circ_002117, novel_circ_001037, and novel_circ_002747, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs, mRNAs, and any other RNAs that share common miRNA response elements (MREs) can competitively bind with miRNAs, acting as an RNA sponge to block and inhibit miRNAs from binding to their target sites ( Tay et al, 2014 ). Studies found that ceRNA regulatory networks are widely present in the growth and development of various insects, such as A. albopictus ( Liu et al, 2023 ), Tetranychus cinnabarinus ( Feng et al, 2022 ), B. mori ( Yin et al, 2021 ). Here, we noticed that 19 DEcircRNAs (novel_circ_002117, novel_circ_001037, and novel_circ_002747, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Different ncRNAs such as lncRNAs and circRNAs, which contain miRNA response elements, are able to interact with miRNAs via competing endogenous networks to further regulate expression of downstream genes [ 63 ]. In insects, ncRNA-involved ceRNA networks were shown to affect and development [ 16 ], metabolism [ 64 ], and immunity [ 65 ]. For example, Wang et al [ 66 ] discovered that the nucleus-enriched lncR26319 in silkworm was able to regulate Endophilin A ( EndoA ), a member of the endophilin family of endocytic proteins, through competitive binding to miR-2834; the lncR26319-miR-2834-EndoA axis was required for Vg endocytosis.…”
Section: Discussionmentioning
confidence: 99%